IMPLEMENTASI KEBIJAKAN PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK (E-KTP) DI KANTOR CAMAT RABA KOTA BIMA - Taufik Irfadat; Niken Ardiansyah; Haeril Haeril (Jurnal Studi Ilmu Pemerintahan, 2021)
The purpose of this study was to determine the friendliness of employees in the implementation of identity card service (E-KTP) in the office of the Camat Raba Kota Bima, and the ability of employees to answer questions and information about the service of identity cards (E-KTP) in the office of the Camat Raba Kota Bima. The population of this study were all 1,100 respondents from 11 Kelurahan, Kecamatan Raba Kota Bima. Sampling using the Quota sampling technique by determining the number of respondents who were set as 100 (one hundred) people accidentally by giving a questionnaire to the respondent. With the type of quantitative research then data collection techniques are observation, questionnaires, and literature study. The collected data were then analyzed with data analysis techniques using SPSs 16.0 for windows and a Likert scale. Most of the service policies for the making of electronic identity cards (e-KTP) stated that they were “good” (70%), which stated “not good” as many (14.5%) of respondents and as many (15.5%) of respondents rated “ not good". The weakness of this dimension lies in the willingness to provide assistance to the community without being asked.